Faktor Integratif Nyama Bali-Nyama Selam: Model Kerukunan Masyarakat pada Era Otonomi Daerah di Bali - I Made Pageh; Wayan Sugiartha; Ketut Sedana Arta, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
In some areas in Bali such as Pegayamana Village (North Bali)and Kepaon Village (South Bali), there are enclave of Muslimscommunity who have long lived in harmony with the BalineseHindu community. Their presence is based on a long historyeven from pre-colonial Bali. These two ethnics with differentreligious background consider themselves relative as can beseen from the integrative expressions of nyama selam (Muslimfamily) and nyama Bali (Balinese family). The former termused by Balinese to honor Muslim, the later used by Muslimto honor Balinese Hindu. They also share similar traditionalpractices like ‘ngejot’, giving food/meal to neighbours duringa religious celebration. This article discusses the integrativefactors that make the relationship between Muslim andBalinese Hindu in some areas in Bali coexist harmoniously.This integrative factors identified to then be developed anddisseminated as guidance to retain harmony or to preventconflict.
Keywords: integrative; nyama Bali; nyama Selam; moslem enclaves